Super-enhancer-associated LINC00963 promotes metastasis of gastric cancer through epithelial-mesenchymal transition - Hong Du; Tingting Xiang; Ying Xia; Yong Jin; Fahua Deng; Wansong Xia; Hongyu Li; Shuqiang Cheng; Bingxue Lan; Sixi Wei; Cunfeng Song; Hai Huang (PLoS ONE, 2025)
Background: In clinical practice, gastric cancer (GC) is a common malignancy with high morbidity. Accumulating research has revealed that lncRNAs are involved in the development and metastasis of tumor tissues in multiple cancers. As reported, LINC00963, a typical lncRNA is aberrantly expressed in gastric cancer. However, the underlying mechanisms of super-enhancers mediating remain unclear. Materials and methods: The GC cell line enhancer-super-enhancer data were downloaded and analyzed from the NCBI database (GSE75595). Combined RT-qPCR and Sanger sequencing were employed to identify three variants of LINC00963 in gastric cell lines and peripheral blood samples from gastric cancer patients. Western blot was used to detect the expression level of epi-thelial-mesenchymal transition (EMT)-related proteins. Transwell assays were applied to assess the cell invasion and migration. A xenograft model was applied to simulate the tumor development process, during which the effect of LINC00963 on promoting tu-morigenesis were investigated. Results: Analysis of the GC cell line enhanc-er-super-enhancer data revealed a high expression of LINC00963 driven by su-per-enhancer. The variant 1 and variant 2 of LINC00963 exhibited high expression in GC cell line and the peripheral blood of gastric cancers. LINC00963 expression in the GC cell line was reduced after exposure to a low dose of the bromodomain and extraterminal inhibitor JQ1. Down-regulation of LINC00963 variant 1 resulted in decreased levels of β-catenin and ZEB1 proteins, and the protein expression levels of several marker proteins related to EMT, such as Vimentin, N-cadherin were observed to decrease (Fig 1). Conclusion: This study demonstrated that the super-enhancer-associated LINC00963 promoting tumor metastasis in gastric cancer through EMT.